2000
DOI: 10.1016/s1097-2765(05)00090-0
|View full text |Cite
|
Sign up to set email alerts
|

The Late Flowering Phenotype of fwa Mutants Is Caused by Gain-of-Function Epigenetic Alleles of a Homeodomain Gene

Abstract: The transition to flowering in Arabidopsis thaliana is delayed in fwa mutant plants. FWA was identified by loss-of-function mutations in normally flowering revertants of the fwa mutant, and it encodes a homeodomain-containing transcription factor. The DNA sequence of wild-type and fwa mutant alleles was identical in the genomic region of FWA. Furthermore, the FWA gene is ectopically expressed in fwa mutants and silenced in mature wild-type plants. This silencing is associated with extensive methylation of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
334
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(345 citation statements)
references
References 47 publications
8
334
0
3
Order By: Relevance
“…3B, panel FWA tr; Lippman et al 2004). The promoter region of FWA in wild-type plants has been shown to be methylated in all sequence contexts (CG, CNG, and CNN) within the two direct repeats region, causing FWA to be silenced (Soppe et al 2000). In this regard, FWA activation in our mutants suggested a possible loss of cytosine methylation and con- sequent heterochromatin disruption.…”
Section: Rnapiva and Rnapivb Act In The Same Pathway And Direct Silenmentioning
confidence: 82%
See 1 more Smart Citation
“…3B, panel FWA tr; Lippman et al 2004). The promoter region of FWA in wild-type plants has been shown to be methylated in all sequence contexts (CG, CNG, and CNN) within the two direct repeats region, causing FWA to be silenced (Soppe et al 2000). In this regard, FWA activation in our mutants suggested a possible loss of cytosine methylation and con- sequent heterochromatin disruption.…”
Section: Rnapiva and Rnapivb Act In The Same Pathway And Direct Silenmentioning
confidence: 82%
“…While the regulation of most genes analyzed was not affected, as exemplified by the floral gene regulator FLC, all independent mutants showed significant expression of the imprinted FWA gene, whose ectopic expression has been shown to induce a late flowering phenotype in Arabidopsis (Fig. 3B, see panels FLC and FWA; Soppe et al 2000). Consistent with the ectopic activation of FWA, we found that the long tandem repeat that encompasses the FWA promoter and the first two untranslated exons is transcriptionally active in all mutants analyzed (Fig.…”
Section: Rnapiva and Rnapivb Act In The Same Pathway And Direct Silenmentioning
confidence: 98%
“…Recent work has shown that FPA, FCA, and homologs of FLD are also required for the repression of loci that are normally associated with high levels of DNA methylation. In fpa fca double mutants, the expression of both AtSN1 and AtMu1 is up-regulated (Baurle et al, 2007) and mutations in the FLD homologs lsd1-like1 (ldl1) and ldl2 lead to ectopic expression of FWA (Jiang et al, 2007), a gene whose DNA is highly methylated and transcriptionally inactive in the sporophyte (FWA is normally expressed the central cell and in endosperm; Soppe et al, 2000;Kinoshita et al, 2004;Ikeda et al, 2007). In some cases, the activation of these normally silenced loci is accompanied by a decrease in DNA methylation, particularly at asymmetric sites (AtMu1 in fpa fca mutants and FWA in ldl1 and ldl2 mutants), whereas, in other cases (AtSN1 in fpa fca mutants), no change in DNA methylation is observed (Baurle et al, 2007;Jiang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Further examples of naturally occurring epialleles are the Colorless nonripening (Cnr) locus in tomato (Manning et al 2006), the transcription factor CmWIP controlling sex determination in melon (Martin et al 2009), the FLOWERING WAGENINGEN (FWA) (Kakutani 1997;Soppe et al 2000;Fujimoto et al 2008Fujimoto et al , 2011 and FOLT1 loci (Durand et al 2012) in Arabidopsis thaliana, and selected SP11 alleles at the complex S locus responsible for self-incompatibility in Brassica rapa (Shiba et al 2006;Tarutani et al 2010). Although no changes in the underlying DNA sequence of the Lcyc and Cnr region have been observed, the epigenetic variants at CmWIP, FWA, FOLT1, and SP11 originate from structural genetic variation.…”
Section: The Molecular Basis Of Epigenetic Variationmentioning
confidence: 99%